Activation and deactivation of the commercial‐type CuO–Cr2O3–Fe2O3 high temperature shift catalyst. Issue 1 (23rd November 2019) - Zhu, Minghui; Tian, Pengfei; Chen, Jiacheng; Ford, Michael E.; Xu, Jing; Wachs, Israel E.; Han, Yi‐Fan
Abstract: This work elucidates the structural evolution of a commercial‐type iron oxide‐based high temperature water–gas shift (HT‐WGS) catalyst during activation and deactivation stages. The findings highlight the importance of Cu–FeO x interfaces. Based on the new insights, future improvement of commercial iron‐based catalysts should focus on stabilization of the active Cu–FeO x interface. Much effort has been devoted to understanding the structure, mechanism, and promotion of the commercial‐type CuO–Cr2 O3 –Fe2 O3 catalyst for the high temperature water–gas shift (HT‐WGS) reaction. However, structural evolution of the catalyst during the activation and deactivation stages was rarely reported. Herein, catalyst characterization, temperature‐programmed studies, and kinetic analysis were conducted on iron oxide‐based HT‐WGS catalysts. Addition of Cu was found to accelerate both the bulk (Fe2 O3  → Fe3 O4 ) and surface (active FeO x –Cu interface) transformations during the catalyst activation stage. During catalyst deactivation, Cu accelerated both sintering of the Fe3 O4 bulk phase and unfavorable encapsulation of the metallic Cu particles with a substantial FeO x overlayer. The loss of the initial active Cu–FeO x interfacial sites reversed the promotional effect of Cu.